Genome-Wide Identification of Essential and Auxiliary Gene Sets for Magnetosome Biosynthesis in Magnetospirillum gryphiswaldense - Karen T. Silva (American Society for Microbiology, 2020)
ABSTRACT Magnetotactic bacteria (MTB) stand out by their ability to manufacture membrane-enclosed magnetic organelles, so-called magnetosomes. Previously, it has been assumed that a genomic region of approximately 100 kbp, the magnetosome island (MAI), harbors all genetic determinants required for this intricate biosynthesis process. Recent evidence, however, argues for the involvement of additional auxiliary genes that have not been identified yet. In the present study, we set out to delineate the full gene complement required for magnetosome production in the alphaproteobacterium Magnetospirillum gryphiswaldense using a systematic genome-wide transposon mutagenesis approach. By an optimized procedure, a Tn5 insertion library of 80,000 clones was generated and screened, yielding close to 200 insertants with mild to severe impairment of magnetosome biosynthesis. Approximately 50% of all Tn5 insertion sites mapped within the MAI, mostly leading to a nonmagnetic phenotype. In contrast, in the majority of weakly magnetic Tn5 insertion mutants, genes outside the MAI were affected, which typically caused lower numbers of magnetite crystals with partly aberrant morphology, occasionally combined with deviant intracellular localization. While some of the Tn5-struck genes outside the MAI belong to pathways that have been linked to magnetosome formation before (e.g., aerobic and anaerobic respiration), the majority of affected genes are involved in so far unsuspected cellular processes, such as sulfate assimilation, oxidative protein folding, and cytochrome c maturation, or are altogether of unknown function. We also found that signal transduction and redox functions are enriched in the set of Tn5 hits outside the MAI, suggesting that such processes are particularly important in support of magnetosome biosynthesis. IMPORTANCE Magnetospirillum gryphiswaldense is one of the few tractable model magnetotactic bacteria (MTB) for studying magnetosome biomineralization. So far, knowledge on the genetic determinants of this complex process has been mainly gathered using reverse genetics and candidate approaches. In contrast, nontargeted forward genetics studies are lacking, since application of such techniques in MTB has been complicated for a number of technical reasons. Here, we report on the first comprehensive transposon mutagenesis study in MTB, aiming at systematic identification of auxiliary genes necessary to support magnetosome formation in addition to key genes harbored in the magnetosome island (MAI). Our work considerably extends the candidate set of novel subsidiary determinants and shows that the full gene complement underlying magnetosome biosynthesis is larger than assumed. In particular, we were able to define certain cellular pathways as specifically important for magnetosome formation that have not been implicated in this process so far.